The Diabetic Kidney - Cortes, Pedro; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2006)
Although diabetic kidney disease is the most prevalent cause of end-stage renal disease and the disease most often leading to chronic renal replacement therapy and kidney transplantation, there has been, in recent years, a steady increase in basic and clinical knowledge of the problem. In The Diabetic Kidney, a stellar group of international researchers and clinicians joins forces to independently survey recent findings, ideas, and hypotheses about the causes and treatment of diabetic nephropathy. Drawing on many years of experience, the authors cover both the basic pathogenic mechanisms of the disease, as well as many of its clinical aspects of identification, management, and new therapeutic approaches. Not always in total agreement, their views reflect the present state of knowledge and its uncertainties, and offer a composite of different authoritative views on the causes of diabetic kidney disease. Highlights include an entire section devoted to novel approaches to studying diabetic nephropathy with the most advanced molecular techniques, and comprehensive descriptions of the most up-to-date views on the diagnosis and treatment of the disease. State of the art and illuminating, The Diabetic Kidney offers both researchers and practicing clinicians a clear understanding of the progress that has been made regarding the pathogenesis of diabetic nephropathy and of the therapeutic interventions needed to prevent its development or treat it.
Basic Pathophysiology and Biochemistry of Diabetic Nephropathy -- Angiotensin II and Its Receptors in the Pathogenesis of Diabetic Nephropathy -- Altered Renal Microvascular Function in Early Diabetes -- Proteinuria and Interstitial Fibrogenesis in Diabetic Nephropathy -- Podocytes and Diabetic Nephropathy -- Altered Glucose Transport and Its Metabolic Effects in Glomerular Cells -- mRNA Translation in Diabetic Nephropathy -- The Hexosamine Biosynthesis Pathway -- Glycation -- Oxidative and Glycooxidative Stress in Diabetic Nephropathy -- Connective Tissue Growth Factor in the Pathogenesis of Diabetic Nephropathy -- Vascular Endothelial Growth Factor as a Determinant of Diabetic Nephropathy -- Transforming Growth Factor-? Signal Transduction in the Pathogenesis of Diabetic Nephropathy -- Hepatocyte Growth Factor -- Proteomics in the Investigation of Diabetic Nephropathy -- Gene Expression Profiling in the Investigation of Diabetic Nephropathy -- PPAR-? Ligands and Diabetic Nephropathy -- ?-Endosulfine in Diabetic Nephropathy -- The Prospect of a Novel Therapeutic, Bone Morphogenetic Protein-7, in Diabetic Nephropathy -- Clinical Aspects of Diabetic Nephropathy -- Genetic Determinants of Diabetic Nephropathy in Type 2 Diabetes -- Major Risks Indicators for Diabetic Kidney Disease -- The Structure of Human Diabetic Nephropathy -- Diabetic Kidney Disease in Transitional and Disadvantaged Populations -- Screening and Treatment of Early Diabetic Renal Disease in Type 1 and Type 2 Diabetes -- Treatment in Advanced Renal Disease in Type 1 and Type 2 Diabetes -- Diabetic Renal and Related Heart Disease -- Management of Diabetic End-Stage Renal Disease With Dialysis -- Diabetic Retinopathy and Nephropathy -- Hypertension and Cardiovascular Disease -- Endothelial Dysfunction -- Anemia and Diabetic Nephropathy.
Keywords: Endocrinology .; Endocrinology